Semiquantitative assessed proteinuria and risk of heart failure: analysis of a nationwide epidemiological database. Issue 9 (7th September 2021) - Fukui, Akira; Kaneko, Hidehiro; Okada, Akira; Yano, Yuichiro; Itoh, Hidetaka; Matsuoka, Satoshi; Morita, Kojiro; Kiriyama, Hiroyuki; Kamon, Tatsuya; Fujiu, Katsuhito; Michihata, Nobuaki; Jo, Taisuke; et al.
Abstract: Background: Heart failure (HF) is increasing in prevalence worldwide. We explored whether adults with trace and positive proteinuria were at a high risk for incident HF compared with those with negative proteinuria using a nationwide epidemiological database. Methods: This is an observational cohort study using the JMDC Claims Database collected between 2005 and 2020. This is a population-based sample [ n = 1 021 943; median age 44 years (interquartile range 37–52); 54.8% men]. No participants had a known history of cardiovascular disease (CVD). Each participant was categorized into three groups according to the urine dipstick test results: negative proteinuria ( n = 902 273), trace proteinuria ( n = 89 599) and positive proteinuria (≥1+; n = 30 071). The primary outcome was HF. The secondary outcomes were myocardial infarction (MI), stroke and atrial fibrillation (AF). We performed multivariable Cox regression analyses to identify the association between the proteinuria category and incident HF and other CVD events. Results: Over a mean follow-up of 1150 ± 920 days, 17 182 incident HF events occurred. After multivariable adjustment, hazard ratios for HF events were 1.09 [95% confidence interval (CI) 1.03–1.15] and 1.59 (95% CI 1.49–1.70) for trace proteinuria and positive proteinuria versus negative proteinuria, respectively. This association was present irrespective of clinical characteristics. A stepwise increase in the risk of MI, stroke and AF with proteinuria category was also observed. Our primary results were confirmed in participants after multiple imputations for missing values and in those having no medications for hypertension, diabetes mellitus and dyslipidemia. The discriminative predictive value for HF events improved by adding the results of urine dipstick tests to traditional risk factors [net reclassification improvement 0.0497 (95% CI 0.0346–0.0648); P < 0.001]. Conclusions: Not only positive proteinuria, but also trace proteinuria was associated with a greater incidence of HF in the general population. Semiquantitative assessment of proteinuria would be informative for the risk stratification of HF. Graphical Abstract: